Designating Longevity Hotspots: Cautions concerning the Instability of per Capita Centenarian Estimates. Issue 1 (February 2013) - Draper, Thomas W.; Christie, Heather; Moore, Chelsea
Estimates of per capita centenarians in a Utah population varied between one per 12, 864 and one per 4, 675, depending on the data that were used, the population assumptions that were made, and the boundary limits that were employed. In general, caution is warranted in claims about the existence of longevity hotspots.